The Synaptonemal Complex Protein ZYP1 Is Required for Imposition of Meiotic Crossovers in Barley . Issue 2 (21st February 2014) - Barakate, Abdellah; Higgins, James D.; Vivera, Sebastian; Stephens, Jennifer; Perry, Ruth M.; Ramsay, Luke; Colas, Isabelle; Oakey, Helena; Waugh, Robbie; Franklin, F. Chris H.; Armstrong, Susan J.; Halpin, Claire
Abstract : The number of genetic crossovers during meiosis, and the potential for creating novel variation, is influenced by the ZYP1 protein. When ZYP1 is depleted in Arabidopsis, fewer crossovers occur, whereas in rice, more crossovers have been reported. Here, we show that barley plants with very reduced amounts of ZYP1 make far fewer crossovers, although the localization of crossovers is not affected. Abstract: In many cereal crops, meiotic crossovers predominantly occur toward the ends of chromosomes and 30 to 50% of genes rarely recombine. This limits the exploitation of genetic variation by plant breeding. Previous reports demonstrate that chiasma frequency can be manipulated in plants by depletion of the synaptonemal complex protein ZIPPER1 (ZYP1) but conflict as to the direction of change, with fewer chiasmata reported in Arabidopsis thaliana and more crossovers reported for rice ( Oryza sativa ). Here, we use RNA interference (RNAi ) to reduce the amount of ZYP1 in barley ( Hordeum vulgare ) to only 2 to 17% of normal zygotene levels. In the ZYP1 RNAi lines, fewer than half of the chromosome pairs formed bivalents at metaphase and many univalents were observed, leading to chromosome nondisjunction and semisterility. The number of chiasmata per cell was reduced from 14 in control plants to three to four in the ZYP1-depleted lines, although the localization of residual chiasmata was not affected. DNA double-strand break formation appeared normal, but the recombination pathway was defective at later stages. A meiotic time course revealed a 12-h delay in prophase I progression to the first labeled tetrads. Barley ZYP1 appears to function similarly to ZIP1/ZYP1 in yeast and Arabidopsis, with an opposite effect on crossover number to ZEP1 in rice, another member of the Poaceae.